miR-6807-5p Inhibited the Odontogenic Differentiation of Human Dental Pulp Stem Cells Through Directly Targeting METTL7A - Wang, Ning; Han, Xiao; Yang, Haoqing; Xia, Dengsheng; Fan, Zhipeng (Frontiers in Cell and Developmental Biology, 2021)
Background: Tooth tissue regeneration mediated by mesenchymal stem cells(MSCs) has become the most ideal treatment. Although the known regulatory mechanism and some achievements have been discovered, directional differentiation cannot effectively induce to regenerate tooth tissue. In this study, we intended to explore the function and mechanism of miR-6807-5p and its target gene METTL7A in odontogenic differentiation. Methods: In this study, human dental pulp stem cells(DPSCs) were used. ALP, ARS and Calcium ion quantification were used to detect the odontogenic differentiation of miR-6807-5p and METTL7A. Real time RT-PCR, Western blot, Dual-luciferase reporter assay and Pull-down assay with biotinylated miRNA were used to confirm that the METTL7A was the downstream gene of miR-6807-5p. Protein-mass spectrometry and Co-IP were used to detect that the SNRNP200 was the co-binding protein of METTL7A. Results: After mineralized induction, the odontogenic differentiation was enhanced in the miR-6807-5p knockdown group and weakened in the miR-6807-5p overexpressed group compared with the control group. The METTL7A was the downstream target of miR-6807-5p. After mineralized induction, the odontogenic differentiation was weakened in the METTL7A knockdown group and enhanced in the METTL7A overexpressed group compared with the control group. SNRNP200 was the co-binding protein of METTL7A. The knockdown of SNRNP200 inhibited the odontogenic differentiation of DPSCs. Conclusions: This study verified that miR-6807-5p inhibited the odontogenic differentiation of DPSCs. The binding site of miR-6807-5p was the 3’UTR region of METTL7A which was silenced by miR-6807-5p. METTL7A promoted the odontogenic differentiation of DPSCs. SNRNP200, a co-binding protein of METTL7A, promoted the odontogenic differentiation of DPSCs.